Die griechische Sagenwelt - Apollodorus,Moser, Christian Gottlob,Vollbach, Dorothea,Moser, Christian G. (Dieterich, 1988)
SW: Sage
Apollodorus <Atheniensis> ist angebl. Verf. - Übers. aus dem Griech
Keywords: Sagenforschung